2020
DOI: 10.3390/app10093333
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Upstream Structures on Downstream Discharge in the Transboundary Imjin River Basin, Korean Peninsula

Abstract: The transboundary river basin is a great challenge for water management and disaster reduction due to its specific characteristics. In this study, upstream impacts from natural and artificial sources on the downstream discharge on the Imjin river basin, the well-known transboundary region in the Korean peninsula, were evaluated using a hydrological model integrating a dam operation module at an hourly timescale. The module uses a concept of the AutoROM method as the operational rule to update the dam storage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…South and North Korea on the Korean Peninsula have been divided since the Korean War (25 June 1950-27 July 1953; due to the special situation of the MDL, two countries have jointly occupied the Imjin River [39]. The Imjin River is the seventh largest river on the peninsula, originating from Duryu Mountain, Beopdong-gun, Gangwon Province, North Korea, passing through MDL, joining the Hantan River and Moonsan Stream, joining the Han River in Gimpo-si, Gyeonggi Province, and then flowing into the West Sea [38].…”
Section: Study Areamentioning
confidence: 99%
“…South and North Korea on the Korean Peninsula have been divided since the Korean War (25 June 1950-27 July 1953; due to the special situation of the MDL, two countries have jointly occupied the Imjin River [39]. The Imjin River is the seventh largest river on the peninsula, originating from Duryu Mountain, Beopdong-gun, Gangwon Province, North Korea, passing through MDL, joining the Hantan River and Moonsan Stream, joining the Han River in Gimpo-si, Gyeonggi Province, and then flowing into the West Sea [38].…”
Section: Study Areamentioning
confidence: 99%
“…This result reflects the absence of a local discharge source within the study area, which may have reflected the decrease in upstream water resources and an absence or scarcity of local resources within the study area due to the lack of precipitation. Many authors have found that the large dams and reservoirs affect the Euphrates' downstream discharge and flow (Yang et al, 2015;Lee et al, 2019;Thu Ha et al, 2020).…”
Section: Discharge Ratesmentioning
confidence: 99%
“…Nitrate (NO3) concentrations were detected at the monitoring stations from 2.25 to 4.55 mg/L. Human Human activities that can increase nutrient levels in aquatic systems include Human activities that can increase nutrient levels in aquatic systems include atmospheric deposition of nitrogen from fossil fuel combustion, agriculture, and industrial activities (Thu Ha et al, 2020). An increase in nutrient concentration with a low-flow situation is particularly harmful if it occurs at a time of the biological activity of living organisms, such as in spring or summer (Lawrence & Gresens, 2004).…”
Section: Water Quality Parametersmentioning
confidence: 99%
“…Such a situation is more severely affected during the dry season when rainfall decreases and river flows are insufficient to repel the saline water, a phenomenon characterized by the appearance in the dry season in coastal areas, but rarely in the upper part of the MD. In addition, the upstream dams influence the discharge through water control [32,33], such as storing water during the rainy season in order to ensure the normal operation of power generation during the dry season [49]. However, it may also impair downstream discharge and irrigation water resources during dry season [33,50].…”
Section: The Effect Of Salinity and Drought Events On Changes In The Ws Ricementioning
confidence: 99%